Investigation into IgG/IgE binding capacity and gut microbiota of digestion products derived from glycated ovalbumin - Jihua Mao; Yanhong Shao; Hui Wang; Jun Liu; Zongcai Tu (Food Science and Human Wellness)
Gut microbiota plays an important role in food allergy. The immunoglobulin G (IgG)/immunoglobulin E (IgE) binding capacity and human gut microbiota changes of digestion products derived from glycated ovalbumin (OVA) were investigated. Gastrointestinal digestion effectively destroyed the primary structure of glycated OVA, resulting in a significantly higher digestibility than gastric digestion, and more abundant peptides < 3 kDa. Moreover, gastric and gastrointestinal digestion products have different fluorescence quenching and red shift of fluorescence peaks, and possess different conformational structures. These changes resulted in a decrease in 28.7% of the IgE binding capacity of gastrointestinal digestion products beyond that of pepsin. Moreover, gastrointestinal digestion products of glycated OVA increased significantly the proportion of Subdoligranulum, Collinsella, and Bifidobacterium. Therefore, gastrointestinal digestion products of glycated OVA altered human intestinal microbiota, reducing the risk of potential allergy.